Covid-19 association with anterior uveitis (post-covid acute anterior uveitis) - Obaid, Naila; Zulfiqar, Rida; Khan, Anam (Journal of the Pakistan Medical Association, 2022)
The Covid-19 outbreak in Wuhan on 31st December 2019 soon became a pandemic. Ocular manifestations in post covid patients have been widely reported. Anterior uveitis is a common form of intraocular inflammation observed on a daily basis by Ophthalmologists. Diagnosis of AAU is relatively simple but identification of its etiology is difficult, specifically with Covid-19. Post Covid-19 AAU is not reported in Pakistan yet. The patient in the given case is investigated thoroughly, no possible cause of AAU is identified. The patient was managed for uveitis. Keywords: Covid-19, uveitis, AAU-acute anterior uveitis.